DESIGN OF INFORMATION SYSTEMS IN HEALTH SERVICES HOSPITALS GANDARIA - Hendri Hendri; Susi Wagiyati, Skom, MM (Jurnal Sistem Informasi, 2001)
Today's progress has touched every aspect of life, including aspects of health care. Inorder to provide good health services, and the sooner it is not wrong if it is acomputerized system should be applied. At Gandaria Hospital currently still usingmanual systems, which in addition to the registration charge for the patient data isalso required to make patient data for new patients, then the data are provided to thereceptionis to be given the serial number checks. However, when relatively fewpatients is not a problem, but problems arise when the number of patients increases,so the registration is required to give a quick and good service. That is why thewriting of this NOA authors hope to provide a snapshot of computerized health careand help simplify the task of the registration.